Criminal Policy in Combating Street Crime in Indonesia - Samsidar Samsidar (Journal of Strafvordering Indonesian, 2025)
Street crime is one of the social problems that continues to be a concern in Indonesia because it has a direct impact on the security and comfort of the community. Criminal policies in overcoming street crime are an important instrument for law enforcement officers and policy makers to reduce the crime rate. This article aims to analyze the effectiveness of criminal policies implemented in overcoming street crime in Indonesia. A normative legal approach is used by analyzing related laws and regulations as well as legal literature and law enforcement reports. The focus of the study includes provisions in the Criminal Code (KUHP), Law Number 2 of 2002 concerning the Indonesian National Police, and Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. The results of the study indicate that although the policy has provided a strong legal basis, enforcement and coordination between institutions still need to be improved so that overcoming street crime can run effectively and sustainably. This study provides recommendations for strengthening policy synergy and community-based preventive approaches.